Synthesis of ω‐hydroxy dodecanoic acid based on an engineered CYP153A fusion construct. Issue 6 (14th August 2013) - Scheps, Daniel; Honda Malca, Sumire; Richter, Sven M.; Marisch, Karoline; Nestl, Bettina M.; Hauer, Bernhard
Summary A bacterial P450 monooxygenase‐based whole cell biocatalyst using Escherichia coli has been applied in the production of ω‐hydroxy dodecanoic acid from dodecanoic acid (C12‐FA) or the corresponding methyl ester. We have constructed and purified a chimeric protein where the fusion of the monooxygenase CYP153A from Marinobacter aquaeloei to the reductase domain of P450 BM3 from Bacillus megaterium ensures optimal protein expression and efficient electron coupling. The chimera was demonstrated to be functional and three times more efficient than other sets of redox components evaluated. The established fusion protein (CYP153AM. aq.‐CPR) was used for the hydroxylation of C12‐FA in in vivo studies. These experiments yielded 1.2 g l–1 ω‐hydroxy dodecanoic from 10 g l–1 C12‐FA with high regioselectivity (> 95%) for the terminal position. As a second strategy, we utilized C12‐FA methyl ester as substrate in a two‐phase system (5:1 aqueous/organic phase) configuration to overcome low substrate solubility and product toxicity by continuous extraction. The biocatalytic system was further improved with the coexpression of an additional outer membrane transport system (AlkL) to increase the substrate transfer into the cell, resulting in the production of 4 g l–1 ω‐hydroxy dodecanoic acid. We further summarized the most important aspects of the whole‐cell process and thereupon discuss the limits of the applied oxygenation reactions referring to hydrogen peroxide, acetate and P450 concentrations that impact the efficiency of the production host negatively.